A is for alligator draw and tell tales from A-Z - De las Casas, Dianne; Gentry, Marita (Libraries Unlimited, 2011)
"A is for alligator: draw and tell tales from A-Z puts that knowledge to work to facilitate the teaching of early literacy skills by connecting learning with kid's love of animals and drawing."